THE CONSTRUCTION OF MUSLIM GEN-Z SPIRITUALITY THROUGH SOCIAL MEDIA AND MOSQUE COMMUNITIES - Muammar Zulfiqri; Alip Nuryanto (Karimiyah: Journal of Islamic Literature and Muslim Society, 2025)
This study investigates how Muslim Generation Z (born 1997–2012) constructs their spirituality through the dual dynamics of social media engagement and mosque community participation in the contemporary digital era. Employing a systematic literature review methodology guided by the PRISMA framework and incorporating thematic analysis of 48 peer-reviewed articles published between 2018 and 2026, the study maps the emerging landscape of digital Islamic piety and examines how online platforms particularly Instagram, TikTok, YouTube, and Twitter/X intersect with physical community institutions such as mosque youth organizations (remaja masjid) in shaping Gen-Z Muslim spiritual identity. The findings reveal three primary mechanisms through which Gen-Z Muslim spirituality is constructed: (1) algorithmic exposure and voluntary content consumption on social media platforms, which democratize religious authority and generate new forms of "formless" or disembodied spirituality; (2) participatory engagement within mosque communities that anchors digital religious experiences in embodied, communal practices; and (3) the hybridization of online and offline religious spaces that produces a distinctive Gen-Z Islamic identity characterized by pragmatism, aesthetic sensibility, and selective religious commitment. The study further identifies critical tensions within this construction process, including the risk of performative piety (riya'), the challenge of religious misinformation, and the erosion of traditional ulama authority. Theoretically, this study contributes to the growing scholarship on digital religion and Muslim youth identity by proposing a "dual-axis spirituality" framework that conceptualizes Gen-Z Muslim religiosity as simultaneously vertical (the individual's relationship with God) and horizontal (social and communal expression). The findings carry significant implications for Islamic education, mosque administrators, and da'wah practitioners seeking to engage Gen-Z Muslims effectively in an increasingly digitalized world.